Students Advocates for Higher Education Scholarship Ceremony 2010 - Students Advocates for Higher Education::::::::::::::: (2024)
Program for the 3rd Annual Student Advocates for Higher Education (SAHE) Scholarship Ceremony. Held on August 6, 2010 at 4:30 PM in the Martin Luther King, Jr. Library.